2011
DOI: 10.4103/0189-6725.86059
|View full text |Cite
|
Sign up to set email alerts
|

Surgical aspects of intestinal tuberculosis in children: Our experience

Abstract: Acute peritonitis, intestinal obstruction and intestinal perforation are the main clinical presentations requiring surgical interventions. Optimal surgical strategy should be adopted to avoid such pitfalls in the management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In a study of 80 adults with ATB by Keshri et al [21], 13 (16.3%) had been on ATT prior to developing complications requiring surgical intervention. Mirza et al reported that 4 of 18 children (22%) on ATT required surgery [22]; most of our patients were diagnosed to have tuberculosis and were on ATT prior to the acute presentation. This calls attention to the need to be constantly vigilant during and even after completion of treatment for ATB, and to be prepared for early intervention in affected children and adults.…”
Section: Discussionmentioning
confidence: 55%
“…In a study of 80 adults with ATB by Keshri et al [21], 13 (16.3%) had been on ATT prior to developing complications requiring surgical intervention. Mirza et al reported that 4 of 18 children (22%) on ATT required surgery [22]; most of our patients were diagnosed to have tuberculosis and were on ATT prior to the acute presentation. This calls attention to the need to be constantly vigilant during and even after completion of treatment for ATB, and to be prepared for early intervention in affected children and adults.…”
Section: Discussionmentioning
confidence: 55%
“…In the case of a subacute presentation, there may be subacute intestinal obstruction, alternation of constipation and diarrhea, palpable abdominal mass, chronic abdominal pain and weight loss [18]. The reported patient had a clinical picture compatible with subacute presentation with abdominal pain and chronic diarrhea, which due to the diagnostic delay was complicated by multiple intestinal perforations at the ileocecal level that required surgical intervention.…”
Section: Discussionmentioning
confidence: 94%
“…Over the last 20 years, the UK has seen a general decline in the incidence of pulmonary TB, but a rise in extrapulmonary TB, especially among non-UK born patients [2,10,13,14]. Worldwide, the risk of abdominal TB in children increases with deterioration in socioeconomic status and increased frequency of HIV infection [8,10,13,15]. As a result, HIV testing is recommended to all patients presenting with TB [1].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal tuberculosis (ATB) accounts for 5% cases of extrapulmonary TB and refers to infection of the gastrointestinal tract (GIT), the mesentery, and its nodes, omentum, peritoneum, and related solid organs [3,5,6]. It usually presents in a clinical spectrum that ranges from non-specific symptoms to those that mimic Crohn's disease or abdominal carcinomatosis [5,[7][8][9]. Peritoneal TB (PTB) is a very rare form of TB and accounts for only 1-2% of cases of TB, 31-58% of cases of abdominal TB [9].…”
Section: Introductionmentioning
confidence: 99%